Effect of desferrioxamine B and Suwannee River fulvic acid on Fe(III) release and Cr(III) desorption from goethite. (1st April 2016) - Stewart, Angela G.; Hudson-Edwards, Karen A.; Dubbin, William E.
Abstract: Siderophores are biogenic chelating ligands that facilitate the solubilisation of Fe(III) and form stable complexes with a range of contaminant metals and therefore may significantly affect their biogeochemical cycling. Desferrioxamine B (DFOB) is a trihydroxamate siderophore that acts synergistically with fulvic acid and low molecular weight organic ligands to release Fe from Fe(III) oxides. We report the results of batch dissolution experiments in which we determine the rates of Cr(III) desorption and Fe(III) release from Cr(III)-treated synthetic goethite as influenced by DFOB, by fulvic acid, and by the two compounds in combination. We observed that adsorbed Cr(III) at 3% surface coverage significantly reduced Fe(III) release from goethite for all combinations of DFOB and fulvic acid. When DFOB (270 μM) was the only ligand present, dissolved Fe(III) and Cr(III) increased approximately 1000-fold and 16-fold, respectively, as compared to the ligand-free system, a difference we attribute to the slow rate of water exchange of Cr(III). Suwannee River fulvic acid (SRFA) acts synergistically with DFOB by (i) reducing the goethite surface charge leading to increased HDFOB + surface excess and by (ii) forming aqueous Fe(III)–SRFA species whose Fe(III) is subsequently removed by DFOB to yield aqueous Fe(III)–DFOB complexes. These observations shed new light on the synergistic relationship between DFOB and fulvic acid and reveal the mechanisms of Fe(III) acquisition available to plants and micro-organisms in Cr(III) contaminated environments.